2015
DOI: 10.3329/bjp.v10i4.23896
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial phycoerythrin purified from marine <i>Lyngbya</i> sp. induces apoptosis in lung carcinoma cells

Abstract: Phycoerythrins from various cyanobacterial sources have been extensively studied globally for their therapeutic potentials. This study shows the apoptotic potential of cyanobacterial phycoerythrin isolated, purified and characterized from marine Lyngbya sp. A09DM on human lung carcinoma cells (A549 cell). Results indicated that purified cyanobacterial phycoerythrin accounted for a dose-dependent decrement in cell viability, mitochondrial membrane potential and an increment in lactate dehydrogenase release. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Altering the cultivation conditions can make the feed beneficial, since it can be enriched with highly valuable metabolites such as omega fatty acids, carotenoids and essential amino acids [ 11 , 50 , 69 , 70 ]. Consequently, the enriched microalgae can be used as feed supplement to improve the quality of their meat, eggs and milk products which will provide multiple health benefits such as anticancer, antioxidant and antiviral effects to humans when consumed [ 20 , 71 , 72 ] (Table 3 ).
Fig.
…”
Section: Nutritional Potential Of Microalgae-based Feedmentioning
confidence: 99%
“…Altering the cultivation conditions can make the feed beneficial, since it can be enriched with highly valuable metabolites such as omega fatty acids, carotenoids and essential amino acids [ 11 , 50 , 69 , 70 ]. Consequently, the enriched microalgae can be used as feed supplement to improve the quality of their meat, eggs and milk products which will provide multiple health benefits such as anticancer, antioxidant and antiviral effects to humans when consumed [ 20 , 71 , 72 ] (Table 3 ).
Fig.
…”
Section: Nutritional Potential Of Microalgae-based Feedmentioning
confidence: 99%
“…Likewise, Deniz and Thangam et al demonstrated the prevention activity of phycocyanin against highly lethal lung cancer using a A549 cell model as well [37,38]. In addition, besides phycocyanin, phycoerythrin, which is also derived from cyanobacteria, has been proven to exert pro-apoptotic and anti-proliferative function in A549 cells [39,40], suggesting the potential pharmaceutical value of phycobiliproteins. Overall, the A549 cell line has been widely used in multiple investigations on functional materials; nevertheless, our study employed H358, H1650; and LTEP-a2 NSCLC cell lines to explore the antineoplastic and underlying mechanism of phycocyanin, which has widely illustrated the biological activities of phycocyanin in NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Huang et al investigated the antineoplastic activity of phycocyanin with a novel perspective by using a phycocyanin-based nanocarrier as a nanoplatform, which exerted highly efficient anticancer efficacy [34]. In addition, besides phycocyanin, phycoerythrin, which also derived from cyanobacterial, was proven to exerted anti-proliferative and pro-apoptotic effects on NSCLC A549 cells [35,36], indicating the potential pharmaceutical value of phycobiliproteins. Overall, as an important type of NSCLC cell line, A549 cells were widely used in multiple investigations on functional foods.…”
Section: Discussionmentioning
confidence: 99%